Qualitative exploration of attitude of Malaysian woman towards complementary and alternative medicines in pregnancy - Ab Rahman, Nur Awanis (2016)
In this developing country, Malaysia, day to day there are many product being marketed in terms of necessity product, healthcare product and so on. In relation to this study, people in Malaysia are being exposed to many complementary and alternative medicines (CAM) that are unsure the safety and efficacy, especially to pregnant women and their baby. It is important to know attitude of pregnant women towards complementary and alternative medicines. The overall aim of this project is to explore the perspectives on CAM use among pregnant women. Study that has been conducted is a qualitative study. Participants are including all pregnant women with difference races. All of the interview session being recorded and consent form has been sign by participants before proceed with the interview session. During analysis of the data, audio that have been taken during the interview are listened by checking on the notes that are taken during the interview session. Thematic analysis was conducted in order to identify themes emerging from the interview scripts. All of the subjects has a positive attitudes towards usage of complementary and alternative medicine without neglecting necessity to consume conventional medicine. Most of them only know about the positive effect of the CAM product without knowing side effect of long term used of that particular CAM product. It is necessary for healthcare providers to have a broad knowledge about complementary and alternative medicines in order to educate pregnant women about their CAM products.